Об учете атмосферной экстинкции при гетерохромной фотометрии звезд - Выборная, Т.В.; Терез, Г.А. (Кинематика и физика небесных тел, 1985)
Рассчитаны коэффициенты атмосферной экстинкции для фотометрической системы UBV и системы φ для звезд различных спектральных классов и классов светимости и разных спектральных кривых прозрачности земной атмосферы. With the aim ot studying the bandwidth effect the atmospheric extinction coefficients are calculated for the photometric system UBV and system φ of the photometer, in which a photomultiplier with stibium-caesium photocathode serves as a receiver, within the airmass interval of 1—4. 35 curves of energy distribution in the spectra of stars of different spectral classes and luminosities and 5 spectral curves of the terrestrial atmosphere transparency characterising the observing sites with excellent, mean and low transparency are assumed as initial data.